MO1048: The Influence of Online Kidney School on Dialysis Choice. (3rd May 2022) - Ørsted Schultz, Anders; Hayes Bauer, Eithne; Kampmann, Jan
Abstract: BACKGROUND AND AIMS: Factors influencing dialysis choice are multifaceted. Detailed and unbiased information is pivotal in order to assist patients in making decisions. Hence, patient education is a cornerstone in the treatment of advanced chronic kidney disease. At the hospital of Southern Jutland, a kidney school has existed for more than 15 years teaching patients about their illness and treatment options at end-stage renal disease (ESRD). Due to the coronavirus disease (COVID-19) pandemic, an online kidney school (OKS) was established. We present the latest results of this ongoing study regarding the change of preferences of ESRD treatment options among patients after participation in online renal education. METHOD: The OKS consists of a 3-h synchronous class taught by a nephrologist and a dialysis nurse combined with asynchronous short films on treatment options and advice from a dietitian. The OKS has been held six times with 45 patients in total. A questionnaire was distributed to participants before and after the OKS. Patients were asked to choose between center haemodialysis, home haemodialysis, peritoneal dialysis, transplantation, maximal conservative medical treatment and 'not enough information to make the decision'. RESULTS: Out of the 45 patients, 36 patients answered the questionnaire before OKS and of those, 19 also answered the questionnaire after OKS. A total of 76% % of the participants were male, 52% answered the questionnaire on their own and 48% answered the questions together with a relative. The percentage of patients not feeling informed enough to make the decision decreased from 56% prior to participation in OKS in comparison to 32% following participation in OKS. The percentage of patients who prefer peritoneal dialysis as their ESRD treatment of choice increased from 6% to 32%. CONCLUSION: Online education on treatment choices for end-stage renal patients leads to change of treatment preferences. This is especially true for peritoneal dialysis. The OKS is designed to help patients make an informed decision on treatment options in ESRD. Although the number of patients feeling unsure about what kind of treatment to choose is decreased, the number of patients unsure about the best treatment option for them remains high. These patients require a follow-up consultation in order for them to make the final decision for ESRD treatment. The number of patients who answered the questionnaire prior to OKS is higher in comparison to after OKS. However, this is an ongoing study and we will be able to confirm or dismiss these preliminary findings at a later stage.